(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article presents a literary analysis of the works of the Bronte sisters and the importance of women’s education in the nineteenth century. The popularity of their works is a pointer that the Brontës had helped readers in the nineteenth century to familiarize themselves with the existence of women writers. The Brontes’ writing helped to inform evolving social mores regarding women and their growing independence during the period and would resonate with subsequent generations of feminists, as well, as they worked to provide equal educations.